Presence of Anisakis nematode larvae in Indian mackerel (Rastrelliger spp.) along the Indian Ocean southern coast of East Java, Indonesia - EKO SETYOBUDI; IZANATUR ROHMAH; RIZKA FAUZIANA SYARIFAH; LISA RAMATIA; MURWANTOKO MURWANTOKO; DINI WAHYU KARTIKA SARI (Society for Indonesian Biodiversity, 2019)
Setyobudi E, Rohmah I, Syarifah RF, Ramatia L, Murwantoko, Sari DWK. 2019. Presence of Anisakis nematode larvae in Indian mackerel (Rastrelliger spp.) along the Indian Ocean southern coast of East Java, Indonesia. Biodiversitas 20: 313-319. In this study, we aimed to determine the prevalence (P), mean intensity (MI) and site of infection of anisakid larvae (Nematoda) in Indian mackerel (Rastrelliger spp.) at the Indian Ocean Southern Coast of East Java. A total of 341 fish were collected from Prigi and Muncar Fish Harbor, East Java during March-April 2018. Each fish specimen was measured in body length and weight, and then dissected for examination of Anisakis larvae in the body cavity, digestive tract, liver, gonad and muscle. The collected larvae were preserved in absolute ethanol for both morphological and molecular identification. The results of this research showed Indian mackerel was susceptible to Anisakis infection (P=17%, MI =6.8 larva/individual fish). Most of the larvae were found in the digestive tract and body cavity, 47.2% and 46.0% respectively. Only a few larvae were found in other internal organs and muscle. Based on morphological identification, these larvae corresponded to Anisakis Type I. Furthermore, in molecular identification using PCR-RFLP, the banding pattern clearly matched with Anisakis typica. The prevalence and mean intensity of Anisakis nematodes on Indian mackerel along the southern coast of East Java seem to be different in each locality and from other adjacent waters as has previously been reported, which may be due to differences in feeding habits and in the distribution of marine mammals as the final host. The results suggest that differences in prevalence and mean intensity of anisakis larvae infection could be developed as a biological indicator of fish stock discrimination. However, clear information regarding food habits of Indian mackerel and migration patterns of the paratenic hosts as well as of marine mammals as final host is needed.